Solid‐State Electrolyte Design for Lithium Dendrite Suppression - Ji, Xiao; Hou, Singyuk; Wang, Pengfei; He, Xinzi; Piao, Nan; Chen, Ji; Fan, Xiulin; Wang, Chunsheng (Advanced materials (Weinheim), 2020)
All‐solid‐state Li metal batteries have attracted extensive attention due to their high safety and high energy density. However, Li dendrite growth in solid‐state electrolytes (SSEs) still hinders their application. Current efforts mainly aim to reduce the interfacial resistance, neglecting the intrinsic dendrite‐suppression capability of SSEs. Herein, the mechanism for the formation of Li dendrites is investigated, and Li‐dendrite‐free SSE criteria are reported. To achieve a high dendrite‐suppression capability, SSEs should be thermodynamically stable with a high interface energy against Li, and they should have a low electronic conductivity and a high ionic conductivity. A cold‐pressed Li3N–LiF composite is used to validate the Li‐dendrite‐free design criteria, where the highly ionic conductive Li3N reduces the Li plating/stripping overpotential, and LiF with high interface energy suppresses dendrites by enhancing the nucleation energy and suppressing the Li penetration into the SSEs. The Li3N–LiF layer coating on Li3PS4 SSE achieves a record‐high critical current of >6 mA cm−2 even at a high capacity of 6.0 mAh cm−2. The Coulombic efficiency also reaches a record 99% in 150 cycles. The Li3N–LiF/Li3PS4 SSE enables LiCoO2 cathodes to achieve 101.6 mAh g−1 for 50 cycles. The design principle opens a new opportunity to develop high‐energy all‐solid‐state Li metal batteries. According to the proposed principles for the suppression of dendrite formation, a Li3N–LiF composite that is thermodynamically stable and has high interface energy against Li metal is designed as an interlayer for dendrite‐free all‐solid‐state batteries. A Li3N–LiF layer coating on a Li3PS4 solid‐state electrolyte achieves a record‐high critical current of >6 mA cm−2 even at a high capacity of 6.0 mAh cm−2.